Bijak Berbahasa dalam Media Sosial: Workshop Penerapan Literasi dalam Media Sosial di Pesantren Nafidatunnajah - I Aeni Muharomah; Lida Holida Mahmud; Yunita Yunita; Tryana Tryana (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2021)
Speak Wisely in Social Media: Workshop on Application of Literacy in Social Media at Nafidatunnajah Islamic Boarding School, a theme that deserves to be brought up considering the fact that misuse of social media can violate the ITE Law and Indonesian netizens are ranked worst in Southeast Asia. The need for social media is unavoidable. Hate speech and bullying through social media often lead to criminal acts, meanwhile the use of social media among students cannot be avoided. Therefore, through our PKM activities, we provide enlightenment, discussion and dialogue regarding how they are the students of the Nafidatunnajah pesantren. Through a persuasive approach, we provide an overview of the facts of positive and negative use in real life. By using case studies and SWOT analysis in developing planning strategies by considering internal and external factors by looking at strengths, weaknesses, opportunities and threats. Through interactive games, all students / students are invited to solve several problems and solutions that must be taken to get input and brainstorming. Furthermore, PKM Team provides directions and solutions on how to use language in social media. By identifying facts and input through dialogue in the field, we conclude that enlightenment and literacy in the use of social media must continue to be carried out so that students realize that in addition to the great benefits that social media offers, there are negative things that can be detrimental.